INVESTIGATION ON THE ADOPTION OF ACTIVITY – BASED STUDENTS’ CENTERED, EXPERIMENT AND IMPROVISATION (ASEI/PDSI) AS AN APPROACH FOR STRENGTHENING MATHEMATICS AND SCIENCE EDUCATION (SMASE) IN PRIMARY SCHOOLS OF NORTH-EASTERN NIGERIA - BODERI, ALI ADAMU; ABUBAKAR MOHAMMED (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
Strengthening of Mathematics and Sciences Education (SMASE) training is an educational innovation and an initiative of the Nigerian government with the support of the Japanese International Cooperation Agency (JICA). It was launched out of the need to improve performance in the crucial Mathematics and science subjects that had been hitherto unimpressive.This study was to find out the level of awareness of ASEI/PDSI as an approach to SMASE among mathematics and science teachers in primary schools of northeastern states and to ascertain the level of attitudinal change among mathematics and science teachers based on ASEI/PDSI principles. The study employed a descriptive survey design, where a questionnaire was used to collect data from the selected 139 mathematics and science subject teachers. The collected data was analyzed using descriptive statistics to determine the mean score and standard deviation to answer the research questions. The result of the study revealed that there is a fair level of awareness of the SMASE programme among the mathematics and science teachers which eventually led to a change in attitude and approach towards teaching mathematics and science. The result also indicated a non-significance difference between the variables tested. Hence the study recommended among others that teachers should be encouraged to adopt ASEI/PDSI as an approach to SMASE.